Using ICPC-2 Standard to Identify Thai Zingiberaceae of Pharmacological Interest - Methee Phumthum; Henrik Balslev (Plants, 2020)
The Economic Botany Data Collection Standard (EBDCS) is a widely used standard among ethnobotanists. However, this standard classifies ethnomedicinal uses into categories based on local peoples’ perception. It is difficult to apply in pharmacological research. The International Classification of Primary Care (ICPC), now updated to ICPC-2, is more related to medical terms, but is rarely used among ethnobotanists. This study aims to apply the ICPC-2 to classify metadata of the ethnomedicinal uses of Zingiberaceae plants in Thailand, in order to identify important medicinal taxa for future research. Data on the ethnomedicinal uses of Thai gingers were collected from 62 theses, journal articles, scientific reports and a book, published between 1990 and 2019. Scientific plant names were updated using The World Checklist of Vascular Plants (WCVP) website. Informant Consensus Factor (ICF) was used to identify the medicinal issues commonly treated with gingers, and the Cultural Importance Index (CI) was used to identify species that might have pharmacological potential. We found records of 76 ginger species with ethnomedicinal uses, and together they had 771 use reports. The gingers were commonly used for treatments related to digestive system conditions, particularly abdominal pain and flatulence. Gingers remain exceedingly important in Thai ethnomedicine, with a high number of useful species. They are used to treat a variety of health conditions, but most commonly such ones that are related to the digestive system. Apart from the popular studied ginger, Curcuma longa, we identified a number of other useful gingers in Thailand.